Study of socio-demographic factors among re-admitted psychiatric patients in relation to their diagnoses in Malaysia - Ali, Syed Masroor; Musa, Ramli; Al-Ani, Ali Sabri Radeef (International Educative Research Foundation and Publisher (IERFP), 2013)
Objectives: The aim of this study is to find out the demographic, and clinical profile of frequently re-hospitalized psychiatric patients. The study will determine relationship between particular psychiatric illness and recurrent admissions. This study investigates and collects all relevant data to reflect the factual situation in Malaysian population. Methods: Cross sectional study of 250 psychiatric patients with different mental illnesses admitted by Psychiatrist in 6 months duration. Patients were included of age 18 years and above and excluded those who were not conversant either in Malay or English language. The questioner with various demographic aspects was used and clinical data of the participants obtained for statistical analysis. Results: It has been noted that there is a significant association between socio-demographic factors and frequent hospitalization of Psychiatric patients in relation to their diagnoses. Conclusion: Patients with mental illnesses have higher prevalence of readmission. Although treatment facilities are available, environmental factors play a vital role in relapse of mental illness and readmission to the Psychiatric wards.